Kawasaki disease complicated with shock syndrome and macrophage activation syndrome in children: a case report - Shu, Juxia; Sun, Jingwei; Li, Jiachen; Wang, Mengjin; Dong, Nan; Qi, Dong; Liu, Fang (Frontiers in Pediatrics, 2025)
Kawasaki disease (KD) is an acute self-limited vasculitis of unknown etiology. Clinically, a small proportion of patients may develop shock syndrome or macrophage activation syndrome (MAS); however, KD shock syndrome (KDSS) complicated by MAS is extremely rare. This article provides a detailed report on the clinical diagnosis and treatment course of a child with KD complicated by KDSS and MAS.